"Counterterrorism Citizens" and the Neurotic City. Issue 1 (1st June 2021) - Batley, Amy
Abstract: An array of methods are used in European cities to respond to terrorism, with counterterrorism infrastructures in the built environment receiving particular academic interest. Yet the significance of imaginations of city spaces are often overlooked in studies of counterterrorism planning. Counterterrorism workshops influence imaginations of urban spaces by encouraging participants to adopt an anticipatory security gaze. This article explores the spatial approach of workshops, which require participants to interpret cities as a series of spaces and locations that could be terror targets. This article proposes that encouraging imaginations of danger in urban spaces can evoke fear, itself an aim of terrorism, or even neurosis, which becomes spatially attached to urban spaces as a means of urban counterterrorism governance.